Volume 5: Heat Transfer, Parts a and B 2011
DOI: 10.1115/gt2011-46330
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Heat Flux for Multi-Hole Cooling Applications

Abstract: The aims of this work are to achieve a better understanding of thermal fluxes around a multi-perforated plate and obtain correlations for heat transfer coefficient on the hot as well as cold side and in a perforation. A 3-dimensional, RANS, conjugate simulation and an adiabatic one are performed for different aerothermal conditions already studied experimentally. Convective heat flux, wall temperature and adiabatic temperature are averaged on a periodic pattern around each hole. A mean heat transfer coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…It may also have consequences regarding the thermal equilibrium of the plate by modifying the mixing between cold and hot gas as well as the relative strengths of the conduction (exchange through the solid plate) and the convection (fluid going through the holes) heat transfers. According to Cottin [17], the heat flux transmitted by conduction within the hole is as large as 37% of the total heat flux (convection and conduction) in the case of the LARA experiment of Miron [53] where M = 3.6 and J = 13; on the contrary, Florenciano [25] found that it was only 8% of the total heat flux in a flow regime corresponding to M = 8.4 and J = 31.…”
Section: DXmentioning
confidence: 99%
“…It may also have consequences regarding the thermal equilibrium of the plate by modifying the mixing between cold and hot gas as well as the relative strengths of the conduction (exchange through the solid plate) and the convection (fluid going through the holes) heat transfers. According to Cottin [17], the heat flux transmitted by conduction within the hole is as large as 37% of the total heat flux (convection and conduction) in the case of the LARA experiment of Miron [53] where M = 3.6 and J = 13; on the contrary, Florenciano [25] found that it was only 8% of the total heat flux in a flow regime corresponding to M = 8.4 and J = 31.…”
Section: DXmentioning
confidence: 99%
“…This correction is employed in the context of steady-state RANS analy ses and can be theoretically applied to every isotropic turbulence model. Bianchini et al [8] introduced a comparison between most used general purpose models and specific treatments developed for film cooling applications [21,23,24] showing that the best match with experimental evidence is achieved for film cooling flows in combination with the k-w shear-stress transport (SST) model.…”
Section: Introductionmentioning
confidence: 97%
“…From a numerical perspective, computational analysis of effu sion systems has proved to be quite challenging due to the high computational cost, related to the large of number of holes com posing the array and to the relatively high pitch to diameter ratio, and simplified modeling deficiency which are characteristic of the jet-in-cross flow scheme [8,19,20] (i.e., overprediction of penetra tion and underestimation of lateral spreading). For these reasons, only recently a proper and effective validation could be performed against experimental data at engine relevant conditions [6,21], These simulations relies on nonconventional turbulence modeling specifically constructed for film cooling phenomena to overcome the above mentioned deficiencies of standard RANS models. Such approach, which consists in a correction of near wall turbulence in case of jet-in-cross flow, is derived from Bergeles's idea of a tensorial definition of eddy viscosity [22] which can be augmented in the stream-span components by means of a doping factor calcu lated algebraically as a function of near wall distance [23].…”
Section: Introductionmentioning
confidence: 99%
“…A first attempt to extend the concept of directional eddy viscosity to other turbulence models was carried out by Cottin et al [55] where the idea of Bergeles was implemented in a SST k − ω model with a benchmarking on a typical combustor liner effusion cooling geometry. Further contribution to this family of models comes from Li et al [56] where a set of general purpose shape functions obtained by higher order computations are used in the tensorial definition of eddy viscosity.…”
Section: Jet In Crossflowmentioning
confidence: 99%
“…Cottin et al [55]. It is implemented in OpenFOAM R code and ANSYS R CFX solver using the same source terms reported in Eq.…”
Section: Implementation In Two-layer Modelmentioning
confidence: 99%